Bifidobacterium response to lactulose ingestion in the gut relies on a solute-binding protein-dependent ABC transporter - Keisuke Yoshida (Nature Portfolio, 2021)
Yoshida et al. investigate the role of an ABC transporter (LT-SBP) in lactulose metabolism and its putative role in enriching the gut microbiota with bifidobacteria that encode this transporter. Their results might help in predicting prebiotics-responder and nonresponder status, helping the clinical interventions testing the efficacy of prebiotics.